Effects of a Brief Mindfulness Induction on Death-Related Anxiety. (August 2019) - Schultz, David M.; Arnau, Randolph C.
This study examined effects of a mindfulness induction on proximal and distal defense responses to mortality salience and negative affect. Three experimental conditions were included: mindfulness, mind-wandering, and worrying. Participants in the mindfulness condition underwent a mindfulness induction at the experiment's outset, while participants in the other two conditions underwent a mind-wandering or worry induction. Inductions involved following guided audio instructions presented via headphones. All conditions ( N = 77) underwent a mortality salience induction after experimental manipulation, involving a written exercise pertaining to one's death. Results indicated fewer proximal responses in the mindfulness and mind-wandering groups, compared with the worrying group, but no differences in distal responses. Negative affect was lower in the mindfulness group than in the worrying group following mortality salience. Results suggest that mindfulness exercises effectively buffer against negative affect and some responses to mortality salience, although these effects are not different from those of mind-wandering.